Aplikasi Edible Coating Pati Kulit Singkong (Manihot utilisima Pohl.) pada Tomat (Solanum Lycopersicum L.) serta Uji Kadar Total Fenol dan Kadar Vitamin C sebagai Sumber Belajar: (Edible Coating Application of Cassava Peel Starch (Manihot utilisima Pohl.) On Tomato (Solanum Lycopersicum L.) and Total Phenolic Content and Vitamin C Test for Learning Resources) - Iqna Yudiyanti; Sabirin Matsjeh (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
Cassava peel was determined to be underutilized by the community that it turned out to be wasted. Cassava peel contains starch which has a potential as an edible coating. During post-harvest, Tomatoes are easily to loose Phenol and Vitamin C. Therefore, there should be solutions to keep Phenol and Vitamin C level on Tomatoes through edible coating application of Cassava Peel Starch. This study aims to find out the effect of edible coating application of cassava peel starch with concentrations of 1%, 2% and 4% on the Total Phenolic Content and Vitamin C in tomatoes on day 3, 6 and 12; as well as to find out the present research’s potential as learning resources for grade VIII of Junior High School in learning Additive Substance. Total Phenolic Content was tested using spectrophotometric, while Vitamin C content was tested using Iodine titration. The results show that the highest Total Phenolic Content and Vitamin C occured on day 12 in the 4% of edible coating treatment, respectively: 0.0525% and 33.2210mg /100g. According to the results, a conclusion could be made that edible coating of cassava peel starch is able to maintain Total Phenolic Content and Vitamin C on Tomatoes, compared to the control. The results of the study could be used as learning resources for grade VIII of Junior High School in learning Additive Substance. Abstrak. Kulit singkong kurang dimanfaatkan oleh masyarakat sehingga menjadi limbah. Kulit singkong mengandung pati yang berpotensi sebagai edible coating. Tomat mudah mengalami kerusakan pasca panen sehingga kadar total fenol dan vitamin C menurun, maka perlu adanya alternatif untuk mempertahankan kadar total fenol dan vitamin C tomat dengan cara aplikasi edible coating pati kulit singkong. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh adanya aplikasi edible coating pati kulit singkong konsentrasi 1%, 2% dan 4% terhadap kadar total fenol dan kadar vitamin C tomat hari ke 3, 6 dan 12 serta mengetahui potensi hasil penelitian sebagai sumber belajar IPA SMP kelas VIII materi zat aditif. Kadar total fenol diuji menggunakan metode spektrofotometri dan kadar vitamin C menggunakan metode titrasi iodium. Hasil penelitian menunjukan kadar total fenol dan kadar vitamin C tertinggi terjadi pada hari ke 12 perlakuan edible coating 4% berturut-turut sebesar 0.0525% dan 33.2210mg/100g, maka edible coating pati kulit singkong dapat mempertahankan kadar total fenol dan vitamin C tomat dibandingkan kontrol. Hasil penelitian dapat digunakan sebagai sumber belajar IPA SMP kelas VIII materi zat aditif.